Un acercamiento a la salud bucal - Bécquer Águila, Jorge Luis; Gispert Abreu, Estela de los Ángeles (Revista Cubana de Estomatología, 2017)
Each year at its inception includes new projects for the improvement of the lives of human beings, and the oral health of populations should never escape the priority of high exponents of states, governments, sectors of society, the economy and the inhabitants of each community in particular.1 The International Dental Federation (FDI) is one of the leading organizations in the efforts to promote oral health policies and actions in all corners of the planet. Any management that can be carried out by decision-makers and beneficiaries of health, to enhance or improve it in all public spaces, can influence the perception of people about the importance of increasing their quality of life.2 The FDI was founded in 1900 in Paris, by a group of six illustrious dentists, headed by Dr. Charles Godon, of France. The initial idea was to organize regular dental congresses to advance the science and art of dentistry and focus the discussion on topics such as dental education, oral hygiene and public dental health. Therefore, long before the development of policies and health education was enshrined in the founding documents of the World Health Organization, the FDI began to develop curricula for the dental profession and strategies to bring oral health to people all over the world.3 An international awareness campaign created and launched by the FDI, adapted and promoted locally by national dental associations in more than 140 countries around the world was launched in 2013 to raise awareness about the importance of good oral health and its importance to safeguard health and general welfare.